Perencanaan Lanskap dan Strategi Pengembangan Potensi Daya Tarik Ekowisata Batu Rongring Taman Nasional Gunung Leuser - Ovie Farizal; Hamdani Harahaf; Marifatin Zahra (Fakultas Teknik, 2020)
Batu Rongring Ecotourism is in the buffer zone of National Park of Gunung Leuser (TNGL). The uniqueness of ecosystems, customs, and flora of the flora makes Batu Rongring Ecotourism interesting to visit. Batu Rongring Ecotourism Planning and Development must be in accordance with the characteristics and potential of the Natural Attraction Attraction (ODTWA) in Batu Rongring. This study aims to analyze landscape planning in developing Batu Rongring ecotourism as a buffer for TNGL. ODTWA potential analysis for the Rongring Stone Development Strategy uses internal factor analysis (IFAS), external factors (EFAS) and SWOT Analysis. Landscape planning is done by involving stakeholders in the Forum Group Disscusion (FGD). The results of the assessment in the development of Batu Rongring Ecotourism is known the value of IFAS = 2.71 which makes the strategy in the development of Rongring Stone is the strength and the value of EFAS = 3.33 establishes the strategy used in developing the Rongring Stone is an opportunity. Batu Rongring Ecotourism has ODTWA that can be developed. Potential ODTWA found in Batu Rongring are: Sei Musam River, Flora fauna, Community huts, Customs, Caves. Batu Rongring Ecotourism development strategies are: Nature Tourism Attraction, Tourism Cooperation, Ecotourism Training, Capital, Sarpras, Economic Tourism, Traditional Tourism, Perdes, Online Promotion.